Grape Colour Phenotyping: Development of a Method Based on the Reflectance Spectrum1. Issue 5 (24th April 2013) - Rustioni, Laura; Basilico, Roberto; Fiori, Simone; Leoni, Alessandra; Maghradze, David; Failla, Osvaldo; de, Victor; Comte, Gilles; Santos‐Buelga, Celestino
ABSTRACT Introduction The colour of fruit is an important quality factor for cultivar classification and phenotyping techniques. Besides the subjective visual evaluation, new instruments and techniques can be used. Objectives This work aims at developping an objective, fast, easy and non‐destructive method as a useful support for evaluating grapes' colour under different cultural and environmental conditions, as well as for breeding process and germplasm evaluation, supporting the plant characterization and the biodiversity preservation. Materials and Methods Colours of 120 grape varieties were studied using reflectance spectra. The classification was realized using cluster and discriminant analysis. Reflectance of the whole berries surface was also compared with absorption properties of single skin extracts. Results A phenotyping method based on the reflectance spectra was developed, producing reliable colour classifications. A cultivar‐independent index for pigment content evaluation has also been obtained. Conclusions This work allowed the classification of the berry colour using an objective method. Copyright © 2013 John Wiley & Sons, Ltd.